Cytokine profile after rubella vaccine inoculation: evidence of the immunosuppressive effect of vaccination - Alexander L. Pukhalsky; Galina V. Shmarina; Maria S. Bliacher; Irina M. Fedorova; Anna P. Toptygina; Julia J. Fisenko; Vladimir A. Alioshkin (Hindawi Limited, 2003)
Background: Immunization with live virus vaccines may cause an immunosuppression with lymphopaenia, impaired cytokine production and defective lymphocyte response to mitogenes. These abnormalities were described in subjects vaccinated against measles. This study was performed to analyse the host immune response related to immunosuppression in subjects vaccinated with live attenuated rubella vaccine.